2017
DOI: 10.1111/ijd.13862
|View full text |Cite
|
Sign up to set email alerts
|

A novel homozygous mutation in PVRL4 causes ectodermal dysplasia‐syndactyly syndrome 1

Abstract: Ectodermal dysplasias (EDs) are a group of hereditary disorders defined by alterations in two or more ectodermal structures. One recently described rare entity is the autosomal recessive inherited ectodermal dysplasia-syndactyly syndrome 1 (EDSS1). Homozygous and compound heterozygous missense and nonsense mutations in the poliovirus receptor related-4 (PVRL4) gene, encoding cell adhesion molecule nectin-4, have been identified as causal for EDSS1. We here report a consanguineous family with a 2-year-old girl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 13 publications
(41 reference statements)
3
15
0
Order By: Relevance
“…Her clinical presentation was unique in that she presented with minimal cutaneous syndactyly. A literature review identified three sporadic EDSS1 cases and six families with two or more affected members ( Table 1 ) [ 4 , 6 , 14 , 16 , 17 , 18 , 19 , 20 ]. The patients originated from Denmark, Turkey, Algeria, Italy, Afghanistan, Pakistan, Azad Jammu and Kashmir.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Her clinical presentation was unique in that she presented with minimal cutaneous syndactyly. A literature review identified three sporadic EDSS1 cases and six families with two or more affected members ( Table 1 ) [ 4 , 6 , 14 , 16 , 17 , 18 , 19 , 20 ]. The patients originated from Denmark, Turkey, Algeria, Italy, Afghanistan, Pakistan, Azad Jammu and Kashmir.…”
Section: Discussionmentioning
confidence: 99%
“…The patients originated from Denmark, Turkey, Algeria, Italy, Afghanistan, Pakistan, Azad Jammu and Kashmir. Consanguinity was reported in seven families [ 4 , 6 , 14 , 17 , 18 , 19 , 20 ]. A proximal bilateral cutaneous syndactyly of both fingers and toes was present in previous cases [ 4 , 14 , 17 , 18 , 19 , 20 ], with the exception of a girl who had involvement limited to toes [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NECTIN4 is highly expressed in the skin (https://www.ncbi.nlm.nih.gov/gene/81607/?report=expression). Mutations in NECTIN4 may cause ectodermal dysplasia-syndactyly syndrome (EDSS1), which is an autosomal disorder [17][18][19]. In our previous study, we found that plasma cadherin 2 (CDH2) was associated with methadone dose change [20].…”
Section: Introductionmentioning
confidence: 99%